AGGREGATIONAL STUDIES OF DIPEPTIDE FROM CLOSTRIDIUM STRAIN MP FLAVODOXIN - CHELLAM JAYNTHY (Asian Journal of Pharmaceutical and Clinical Research, 2014)
With recent innovations in the field of nanosciences, research has shown tremendous advances in the arena of drug carriers. In this aspect, our work comes out with a novel dipeptide Boc-Val-Val-NHMe which has been synthesized, characterized and its aggregational behavior studied in non aqueous medium. The peptides forms inverted micelles at different temperatures ranging from 297 to 390 Kelvin. Inverted micelles are discrete particles with the hydrophilic ends clustered together leaving the hydrophobic moieties to interact with the solvent (hydrophobic) medium. These Â micelles find diverse applications. Â  Keywords: Micelles, critical micelle concentration, dipeptide, aggregation, aggregation number